Ambivalent sovereigns and restorative justice: exploring conditions of possibility and impossibility for restorative justice in a post-communicative age - Lippens, Ronnie (Critical criminology, 2015)
This contribution hopes to be able to contribute to answering the question: whither restorative justice? The restorative justice (RJ) movement has arrived at an existential crossroads. In this contribution an attempt is made to analyse how some of the origins of the RJ movement could be located in the emergence and crystallization of a new form of life ("control society") in the wake of the Second World War. At the heart of this form of life one might be able to discern, on the one hand, a desire for and will to radical sovereignty, and, on the other, a resulting awareness of ambivalence. Whilst these aspects of post-war life have formed the backdrop of developments in RJ, and have therefore formed part of its conditions of possibility, one might now wonder if, in a post-communicative age such as ours, those very aspects have now become part of its conditions of impossibility. The argument explored in this contribution however holds that elements in the aforementioned form of life also hold potential for the re-thinking of restorative justice theory and practice.